Abnormal room temperature phosphorescence of purely organic boron-containing compounds: the relationship between the emissive behaviorand the molecular packing, and the potential related applications. Issue 12 (26th October 2017) - Chai, Zhaofei; Wang, Can; Wang, Jinfeng; Liu, Fan; Xie, Yujun; Zhang, Yong-Zheng; Li, Jian-Rong; Li, Qianqian; Li, Zhen
Abstract : Long-lived RT phosphorescence was achieved with a series of organic boron-containing compounds due to the rigid conformation and effective π–π stacking in the solid states. Abstract : Purely organic materials with the characteristic of room-temperature phosphorescence (RTP) under ambient conditions demonstrate potential benefits in advanced optoelectronic applications. Exploration of versatile and efficient RTP compounds with low prices is full of challenges due to the slow intersystem crossing process and ultrafast deactivation of the active excited states of organic compounds. Here, a series of boron-containing phosphors were found to present RTP with long-lived lifetimes. Among these commercially available and cheap compounds, (4-methoxyphenyl)boronic acid (PBA-MeO) exhibits long-lived RTP, with a lifetime of 2.24 s, which is among the longest lifetimes of single-component small molecules. Our extensive experiments illustrate that both a rigid conformation and expanded conjugation induced by molecular alignment contribute to the persistent RTP. Because of strong intermolecular interactions via hydrogen bonds, these arylboronic acids easily form crystals and are quite appropriate for anti-forgery materials. Subsequently, we develop a precise, speedy and convenient inkjet printing technology for the fabrication of optoelectronic displays. Furthermore, PBA-MeO is used as an additive to feed Bombyx mori silkworms and shows low toxicity over inorganic materials. Our findings may pave a new way for the development of RTP phosphors and promote their use in practical applications.